Outcome of COVID-19 in allogeneic stem cell transplant recipients: Results from the EPICOVIDEHA registry - Busca, Alessandro; Salmanton-García, Jon; Marchesi, Francesco; Farina, Francesca; Seval, Guldane Cengiz; Van Doesum, Jaap; De Jonge, Nick; Bahr, Nathan C.; Maertens, Johan; Meletiadis, Joseph; Fracchiolla, Nicola S.; Weinbergerová, Barbora; et al. (Frontiers in Immunology, 2023)
Background. The outcome of COVID-19 in allogeneic hematopoietic stem cell transplantation (HSCT) recipients is almost uniformely considered poor. The aim of present study was to retrospectively analyse the outcome and risk factors for mortality in a large series of patients who developed COVID-19 infection after an allogeneic HSCT. Methods. This multicenter retrospective study promoted by the European Hematology Association – Infectious Diseases Working Party, included 326 adult HSCT patients who had COVID-19 between January 2020 and March 2022. Results. The median time from HSCT to the diagnosis of COVID-19 was 268 days (IQR 86-713; range 0.185 days). COVID-19 severity was mild in 21% of the patients, severe in 39% and critical in 16% of the patients. In multivariable analysis factors associated with a higher risk of mortality were, age above 50 years, presence of 3 or more comorbidities, active hematologic disease at time of COVID-19 infection, development of COVID-19 within 12 months of HSCT, and severe/critical infections. Overall mortality rate was 21% (n=68): COVID-19 was the main or secondary cause of death in 16% of the patients (n=53). Conclusions. Mortality in HSCT recipients who develop COVID-19 is high and largely dependent on age, comorbidities, active hematologic disease, timing from transplant and severity of the infection.